EARLY CHILDHOOD PARENTING SHIFTS IN INDRAMAYU FAMILIES WITH OVERSEAS MIGRANT WORKING MOTHERS - Windiana, Wiwin; Lubis, Sopian; Asfiya’ R, M. Syauqi (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Poverty frequently causes husbands and wives to face many issues in their marriages. It encourages wives to work as overseas migrant working mothers to help their husbands earn a living. This research investigates the shift in parents' role in early childhood parenting in the overseas migrant working mother family. The investigation is Both changes in mother's Parenting before and after becoming workers abroad, as well as changes in parenting from mother to caregiver while the mother is abroad, such as father, older sister, and grandmother. Furthermore, this research investigated the impacts of early childhood parenting shifts in families with overseas migrant working mothers to the children. The research used a descriptive qualitative method. We used an interactive model of data analysis that began with data collection and continued with data reduction, data display, and conclusion drawing and verification. The results showed that The two respondents who became mothers while working abroad had the same parenting style before and after going abroad to work, which is authoritative Parenting. In addition, The grandmother who takes care of the grandchildren when their mother is away also using the same parenting style as the mother. However, The parenting style has evolved when a child is cared for by an older sister and her father. The older sister employs authoritative Parenting. The father's parenting style, on the other hand, is permissive. The advantage of this research is that it provides an overview of Parenting that caregivers should provide to children so that children can receive care similar to that of their mothers. Furthermore, this is to investigate the impacts of each parenting method used by the mother and caregiver.